The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/biom12060855
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Assisted Synthesis and Characterization of Zinc Oxide Nanoparticles from Lepidium sativum and Their Potent Antioxidant, Antibacterial and Anticancer Activities

Abstract: Nanotechnology is an emerging area of research that deals with the production, manipulation, and application of nanoscale materials. Bio-assisted synthesis is of particular interest nowadays, to overcome the limitations associated with the physical and chemical means. The aim of this study was to synthesize ZnO nanoparticles (NPs) for the first time, utilizing the seed extract of Lepidium sativum. The synthesized NPs were confirmed through various spectroscopy and imagining techniques, such as XRD, FTIR, HPLC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 72 publications
3
16
0
Order By: Relevance
“…Surface modifications and hybridization of the synthetic ZnO particles by the different physical and chemical methods were suggested as enhancement techniques for their biocompatibility, biological activity, and genotoxicity in addition to their antibacterial and antioxidant properties [15,18,26]. The commonly used modification techniques are: (1) elemental doping of ZnO crystal structure, (2) integrating the ZnO particles in composites with other metal oxides, (3) supporting the synthetic ZnO particles into effective carriers or substrates, (4) integrating the synthetic ZnO particles in composites with biologically active biopolymers, and (5) synthesis of the ZnO grains in chemical complexes with the known active phytochemicals from the extracts of the plants [14,20,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Surface modifications and hybridization of the synthetic ZnO particles by the different physical and chemical methods were suggested as enhancement techniques for their biocompatibility, biological activity, and genotoxicity in addition to their antibacterial and antioxidant properties [15,18,26]. The commonly used modification techniques are: (1) elemental doping of ZnO crystal structure, (2) integrating the ZnO particles in composites with other metal oxides, (3) supporting the synthetic ZnO particles into effective carriers or substrates, (4) integrating the synthetic ZnO particles in composites with biologically active biopolymers, and (5) synthesis of the ZnO grains in chemical complexes with the known active phytochemicals from the extracts of the plants [14,20,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…17 This coordination interaction may result in the reduction of metal ions while lupulon itself could undergo oxidation, leading to the formation of corresponding oxidation by-products. 8…”
Section: Resultsmentioning
confidence: 99%
“…17 This coordination interaction may result in the reduction of metal ions while lupulon itself could undergo oxidation, leading to the formation of corresponding oxidation by-products. 8 Scheme 1 also illustrates the proposed mechanism for the formation of WHE-ZnO NZs by WHE. In this mechanism, the labeled out phenolic hydroxy groups (in green) in lupulon are particularly significant in the synthesis of the NZs.…”
Section: Green Synthesis Of the Whe-zno Nzsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best metal chelating ability was recorded in the combined group with 36.80 mg EDTAE/g, followed by RA (36.59 mg EDTAE/g), Nar (35.92 mg EDTAE/g) and the control (31.81 mg EDTAE/g). Although several studies have reported phosphomolybdenum (PMB) and metal chelating abilities of L. sativum, [47][48][49][50] there is no data on the effects of modulators on these abilities. After combining and analyzing all the results, it became clear that the modulators significantly improved the antioxidant ability of the root samples.…”
Section: Antioxidant Effectsmentioning
confidence: 99%